Graciela Batticuore, Mariquita Sánchez. Bajo el signo de la revolución, Buenos Aires, Edhasa, 2011, 316 páginas. - Fontana, Patricio (2014)
Fil: Fontana, Patricio. Universidad de Buenos Aires; Argentina.